Land tenure and implementation of REDD+ in Central Africa - Karsenty, A.; Assembe-Mvondo, Samuel (2011)
Central African countries are elaborating strategies for the implementation of the main elements of the REDD+ mechanism (Reducing Emissions from Deforestation and Forest Degradation). Among the measures needed to avoid deforestation and to introduce indicative systems for the conservation of forests, reforms to adapt land tenure systems to international agendas fixed by the major conventions on environment are the most important. In customary systems, the appropriation of land by families is handed down through “wood chopping” rights (droit de hache) the visible transformation of the environment through activities such as deforestation. In modern tenure systems, the constitution of private property passes through environmental enhancement – clearing as an initial condition of development. Responding to the populations’ security of tenure aspirations and, at the same time, adapting the incentives in favour of forest conservation as opposed to their conversion to agriculture, involves working on the tenure rights and the recognition of local collective heritage by putting in place parallel systems of remuneration when deforestation is avoided, which should not be confused with the distribution of “carbon rights”.